2018
DOI: 10.2478/sjph-2018-0005
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for osteoporosis in postmenopausal women – from the point of view of primary care gynecologist

Abstract: IntroductionOsteoporosis is a highly prevalent public health problem with osteoporosis-related fractures that account for high morbidity and mortality. Therefore, prevention strategies and early detection of osteoporosis should be carried out in primary gynaecological care units, so as to substantially reduce the risk of fractures and allow the best treatment option for a particular woman.MethodsFrom 2002 to 2011, we recruited 2956 women. Of the total number of women, we additionally extrapolated 1274 women ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…According to the WHO, 30% of women over the age of 50 have osteoporosis [19]. Similarly, a recent study estimated that 29.9% of postmenopausal women in the United States had osteoporosis [20], and a study conducted in Slovenia found that the prevalence of osteoporosis increased with age from 24.9% in patients aged 60-64 y to 37.4% in patients aged 70-75 y [21]. However, the reported prevalence of osteoporosis in women varies widely across countries with 9% reported in the United Kingdom, 15% in France and Germany, 16% in the United States, and a prevalence of 38% reported in Japan [22].…”
Section: Discussionmentioning
confidence: 99%
“…According to the WHO, 30% of women over the age of 50 have osteoporosis [19]. Similarly, a recent study estimated that 29.9% of postmenopausal women in the United States had osteoporosis [20], and a study conducted in Slovenia found that the prevalence of osteoporosis increased with age from 24.9% in patients aged 60-64 y to 37.4% in patients aged 70-75 y [21]. However, the reported prevalence of osteoporosis in women varies widely across countries with 9% reported in the United Kingdom, 15% in France and Germany, 16% in the United States, and a prevalence of 38% reported in Japan [22].…”
Section: Discussionmentioning
confidence: 99%
“…This could be related to the impact of aging on bone density, muscle strength, and balance in the older population, which increases the risk of falling and consequently increases the risk of spinal fractures. 25 , 27 , 28 In addition, a significantly higher frequency of FFH was identified among non-Kuwaitis. Ultimately, preventive programs could be directed toward two routes: (1) increasing traffic safety measures for younger adults; (2) reducing the effect of aging on bone density, strength, and balance in older adults by increasing their awareness through public health systems, and through preventive programs; and (3) increasing work-related safety measures for non-Kuwaiti workers.…”
Section: Discussionmentioning
confidence: 93%
“…The reduction in the prevalence of spinal fractures in men over the age of 50 years old could be related to the post-menopausal osteoporotic factor in women, where at the age of 50, the risk of fractures due to osteoporosis reaches 40%, and this increases women’s risk of sustaining spinal traumatic fractures. 25 This observation suggests that osteoporosis could be an important factor to consider in future research and preventive programs. In addition, spinal fractures were found to be more prevalent among Kuwaitis.…”
Section: Discussionmentioning
confidence: 99%
“…1 It is a systemic chronic bone disease without obvious clinical symptoms, and it is mainly caused by postmenopausal ovarian dysfunction, decrease of estrogen level, and degeneration of bone microstructure. 2 The incidence of pathological fracture, a serious complication of OP, is more than 70%. 3 With the rapid rise in the proportion of the elderly population, the incidence rate of OP has also increased significantly.…”
Section: Introductionmentioning
confidence: 99%